Ingeborg Levin (1953-2024): pioneer in radiocarbon and atmospheric research - Vogel, Felix; Hammer, Samuel (Science, 2024)
Ingeborg Levin, groundbreaking physicist who helped quantify the carbon cycle and greenhouse gas emissions, died on 10 February. She was 70. Ingeborg established high-quality long-term measurements to identify the radiocarbon present in carbon dioxide and inform estimates of carbon fluxes. In the late 1970s, climate change and greenhouse gases were far from a mainstream interest, but Ingeborg immediately recognized their importance and the crucial role science would play in informing policy. She also realized early on that the carbon-14 (14C) introduced into the atmosphere by nuclear weapons testing presented a singular opportunity to understand how carbon moves from the atmosphere into other carbon reservoirs, such as the biosphere, soils, and oceans.
Gesehen am 04.12.2024